PENGARUH ALAT PERAGA KINEMATIKA GLB DAN GLBB UNTUK PENGUATAN PEMAHAMAN TENTANG GERAK DI KELAS IV SDN KEBONAGUNG 02 JEMBER - Fadilla, Nur; Irma Yunita Sari; Muhammad Suwignyo Prayogo (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
The purpose of this research article is to determine the effect of GLB and GLBB kinematics props to strengthen students’ understanding of motion in class IV SDN Kebonagung 02 Jember. The method used is quantitative with the type of pre-experimental design and the form of one group pretest posttest design. This research technique uses field research techniques with test instruments and questionnaires. Data analysis using the N-Gain test, normalization test, T test on test results and elaboration on questionnaire results. The results showed that the N-Gain test was found to be 0.60 which means the medium category and normally distributed through the normality test. Likewise, the T-test results show that after the use of props, the t value is 8.816 with sig. (2-tailed) 0.000 which means that there is a significant difference in student understanding before and after being given exposure through kinematics props. So it can be concluded that the use of kinematics props has an effect on strengthening students’ understanding of motion for grade IV students at SDN Kebonagung 02 Jember.